A methodological approach for direct quantification of the activated sludge floc size distribution by using different techniques - Govoreanu, R (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
The activated sludge floc size distribution (FSD) is investigated by using different measurement techniques in order to gain insight in FSD assessment as well as to detect the strengths and limitations of each technique. A second objective was to determine the experimental conditions that allow a representative and accurate measurement of activated sludge floc size distributions. Laser diffraction, Time Of Transition (TOT) and Dynamic Image Analysis (DIA) devices were connected in series. The sample dilution liquid, the dilution factor and hydraulic flow conditions avoiding flocculation proved to be important. All methods had certain advantages and limitations. The MastersizerS has a broader dynamic size range and provides accurate results at high concentrations. However, it suffers from an imprecise evaluation of small size flocs and is susceptible to particle shape effects. TOT suffers less from size overestimation for non-spherical particles. However, care should be taken with the settings of the transparency check. Being primarily a counting technique, DIA suffers from a limited size detection range but is an excellent technique for process visualization. All evaluated techniques turned out to be reliable methods to quantify the floc size distribution. Selection of a certain method depends on the purpose of the measurement